Case Report: Prenatal and Postnatal Management for Fetal Bronchogenic Cysts During the COVID-19 Pandemic - Cheng, Lin; Duan, Jie; Wang, Mei; Lu, Dan; Li, Huan; Ma, Jianhong; Liu, Juan; Wang, Cheng; Zhang, Yuanzhen (Frontiers in Pediatrics, 2021)
Background: Fetal bronchogenic cyst (BC) is a rare congenital anomaly with an incidence of 0.147‰ to 0.238‰. COVID-19 pandemic, as a particular situation, hindered pregnant women from receiving periodic prenatal checkups. Case description: Until 34+6 weeks of gestation, a fetal case of the intrathoracic cyst was found by ultrasound examination. Further MRI examination confirmed the diagnosis of the congenital mediastinal cystic lesion, probably BC. Genetic testing was not conducted due to the COVID-19 pandemic. At 38+5 weeks of gestation with maternal COVID-19 testing negative, a live girl was delivered by cesarean section. Five months later, the child underwent bronchocystectomy, and the postoperative pathological lesions confirmed a (right upper mediastinum) bronchogenic cyst. Conclusion: Herein, we reported the prenatal and postnatal management for a rare case of the congenital bronchogenic cyst by multidisciplinary approaches during the COVID-19 pandemic. Especially, fetal MRI and screening for fetal chromosomal abnormalities are recommended. This case contributes to the awareness that the COVID-19 pandemic interferes with regular follow-up schedules during pregnancy that may interfere with timely performed additional tests, and finally results in more accurate genetic counseling. A combination of multidisciplinary approaches, including radiology, infection, genetic counseling, obstetrics, and pediatric surgery, is pivotal for managing fetal bronchogenic cyst during the COVID-19 pandemic.